THE ROLE OF SUBJECT POSITION IN SENTENCE COMPREHENSION IN ENGLISH - Siburian, Tria Joys; Situmorang, Leony Elisabeth; Panjaitan, Frans Seda (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2024)
The role of subject position in sentence comprehension has been a topic of much debate in the field of linguistics. Some researchers argue that the subject position plays a crucial role in determining the overall meaning of a sentence, while others suggest that other factors, such as word order or context, maybe more important. In this paper, we will examine the evidence for and against the importance of subject position in sentence comprehension, and discuss how different theoretical frameworks can account for these findings. For example, in the sentence "The dog chased the cat," the subject position (the dog) determines who is acting chasing. However, in a passive construction like "The cat was chased by the dog," the subject position is less important for understanding the overall meaning of the sentence. While the subject position may play a role in sentence comprehension, it is not the sole determining factor. Other factors such as word order and context also contribute to understanding the meaning of a sentence. Different theoretical frameworks, such as generative grammar or cognitive linguistics, offer varying explanations for how language is processed and understood. Generative grammar focuses on the underlying structure of sentences and how they are formed, while cognitive linguistics emphasizes the role of cognitive processes in language comprehension. Both frameworks acknowledge the importance of factors beyond the subject position in understanding sentence meaning, highlighting the complex nature of language processing. By considering these different perspectives, researchers can gain a more comprehensive understanding of how language functions and how it is interpreted by speakers and listeners